Трудові права у системі прав людини і громадянина - Андріїв, В. М.; Андреев, В.М.; Andreev, V. (My University, 2011)
The article deals with the role and place of labour rights in the system of human and civil rights. Author gives the proposals for improving provisions of the draft Labor Code of Ukraine in the sphere of rights of employees and employers.
Андріїв В. М. Трудові права у системі прав людини і громадянина / В. М. Андріїв // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспрт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 42. – С. 241- 247.
Keywords: трудові права; система прав людини і громадянина; права людини і громадянина; проект Трудового кодексу України; права робітників та роботодавців; трудовые права; система прав человека и гражданина; права человека и гражданина; rights of employees and employers; права сотрудников и работодателей; the draft Labour Code of Ukraine; проект Трудового кодекса Украины; human and civil rights; system of human and civil rights; labor rights